1994
DOI: 10.1021/bi00187a042
|View full text |Cite
|
Sign up to set email alerts
|

A Model Membrane Approach to the Epidermal Permeability Barrier

Abstract: The permeability barrier of mammalian skin is found in unusual intercellular domains in the upper layers of the epidermis, and is composed mainly of three lipid classes: ceramide, cholesterol, and free fatty acid. These are organized as lamellae, but the details of lipid organization are not precisely known. To examine the relationship between lipid composition and phase behavior, aqueous dispersions of bovine brain ceramide, cholesterol, and perdeuterated palmitic acid were examined by 2H NMR and compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
107
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 51 publications
26
107
0
Order By: Relevance
“…Comparisons of stratum corneum extracted lipids with dmpc and dmpc-cholesterol bilayer systems have suggested that liquid crystalline phase dmpc-cholesterol bilayers would be a reasonable model of stratum corneum lipids for diffusion coefficients of solute molecules 22,24,31 and is further corroborated by the agreement for the calculated and experimental fentanyl flux. However, the effects of permeation enhancers on dmpc/cholesterol bilayer systems might be different from their effects on stratum corneum lipids, and experimental verification of the degree to which oleic acid increases fentanyl flux is needed.…”
Section: Discussionmentioning
confidence: 67%
“…Comparisons of stratum corneum extracted lipids with dmpc and dmpc-cholesterol bilayer systems have suggested that liquid crystalline phase dmpc-cholesterol bilayers would be a reasonable model of stratum corneum lipids for diffusion coefficients of solute molecules 22,24,31 and is further corroborated by the agreement for the calculated and experimental fentanyl flux. However, the effects of permeation enhancers on dmpc/cholesterol bilayer systems might be different from their effects on stratum corneum lipids, and experimental verification of the degree to which oleic acid increases fentanyl flux is needed.…”
Section: Discussionmentioning
confidence: 67%
“…Lipids within the SC are organized in layers called lamellae, but the details of how individual lipid molecules are involved in the organization of the SC remain obscure (Kitson et al, 1994;Bouwstra et al, 2003;Hill and Wertz, 2003). It is thought that ceramides form the structural backbone of the lamellae, and those containing linoleic acid serve to rivet bilayers together (Bouwstra et al, 2003;Lillywhite, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the hexagonal (HEX) phase, the all-trans lipid chains have some rotational mobility along their long axes, but their translational mobility is restricted. In the liquid-crystalline (LIQ) phase, the chains have a high degree of gauche isomerization and their lateral organization is completely lost; the chains have both high rotational and high translational mobility in the plane of the membrane.Data from FTIR, WAXD, 2 H NMR and electron diffraction have shown that all three phases are present in healthy human SC, with a notable prevalence of the OR phases [83][84][85][86][87], contrary to an earlier model of a single gel-phase matrix [88]. Thus, the average packing density in the SC lipid lamellae is higher than the one Figure 3 A scheme illustrating the three-dimensional structure of the lipid lamellae.…”
mentioning
confidence: 96%